Identifikasi Permasalahan Pembelajaran IPS di Semua Tingkat Pendidikan Formal (SD, SMP dan SMA) - Ajeng Dwi Pratiwi; Amini Amini; Elsa Manora Nasution; Fitri Handayani; Neng Putri Mawarny (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
This paper will describe some of the problems that are often encountered in learning Social Sciences (IPS). In addition, social studies learning problems will be explained from the lowest level of education, namely elementary, middle and senior levels. Social studies learning problems for each level of formal education will certainly have differences in each problem. Social studies lessons given at the elementary school level are given by examining several events, concepts, facts and generalizations and related to social issues which contain social studies material, namely geography, economics, history and sociology. Meanwhile, IPS learning at the secondary school level is given in an integrated or comprehensive manner, which is commonly known as Integrated IPS. At the middle school level, social studies lessons have been given separately, such as history lessons, economics lessons, sociology lessons and geography lessons have been taught separately. Each level of education has differences in the application of IPS learning in the learning process, therefore the identification of social studies learning problems will be different for each level of education. When IPS learning is given in an integrated and separate manner, different problems will arise between the two. Social studies learning is known as boring learning, therefore here we will explain some of the social studies learning problems that exist at every level of formal education in Indonesia. Keywords: Problems, Learning, IPS